Molecular Aspects of Dendritic Cell Activation in Leishmaniasis: An Immunobiological View - Tibúrcio, Rafael (Front Immunol, 2019)
Dendritic cells (DC) are a diverse group of leukocytes responsible for bridging innate and adaptive immunity. Despite their functional versatility, DCs exist primarily in two basic functional states: immature and mature. A large body of evidence suggests that upon interactions with pathogens, DCs undergo intricate cellular processes that culminate in their activation, which is paramount to the orchestration of effective immune responses against Leishmania parasites. Herein we offer a concise review of the emerging hallmarks of DCs activation in leishmaniasis as well as a comprehensive discussion of the following underlying molecular events: DC-Leishmania interaction, antigen uptake, costimulatory molecule expression, parasite ability to affect DC migration, antigen presentation, metabolic reprogramming, and epigenetic alterations.